DEATH DUE TO CHOKING - A CASE STUDY (Journal of Forensic Medicine & Toxicology, 2015)
Common Asphyxial deaths include Hanging and Strangulation. Hanging being suicidal in nature and Strangulation homicidal. A little data is published on cases of Choking and its causes and effects. Here one such rare case of choking is discussed where a 24 year old male was brought dead to the mortuary, Rajarajeswari Medical College and Hospital for autopsy with history of accidental fall into the sand crusher machine while at work. The cause of death and other aspects of this case are being discussed here.
Keywords: Accidental choking; Asphyxia; Foreign bodies